A Systemic Challenge to the Reliability and Admissibility of Firearms and Toolmark Identification - Schwartz, Adina (Science and Technology Law Review, 2005)
Firearms identification, often improperly referred to as “ballistics identification,” is part of the forensic science discipline of toolmark identification. Despite widespread faith in “ballistics fingerprinting,” this article contends that because of systemic scientific problems, firearms and toolmark identifications should be inadmissible across-the-board. This article explains that similarities between toolmarks made by different tools and differences between toolmarks made by the same tool imply that a statistical question must be answered to determine whether a particular tool was the source of an evidence toolmark. What is the likelihood that the toolmarks made by a randomly selected tool of the same type would do as good a job as the toolmarks made by the suspect tool at matching the characteristics of the evidence toolmark? Firearms and toolmark examiners evade this question by claiming to be able to single out a particular firearm or other tool as the source of an evidence toolmark. The article further explains that the absence of statistical empirical foundations cannot be excused on the ground that, regardless of how they do it, firearms and toolmark examiners reach accurate identity conclusions. Although firearms and toolmark examiners have feared that Daubert would lead courts to exclude their testimony, both before and after Daubert, firearms and toolmark identification testimony has largely been admitted as a matter of course. No court, including the two recent courts that have excluded particular identification testimony, has recognized the systemic scientific problems with the field. Nonetheless, because of the risk that innocent people will be convicted or even sentenced to death on the basis of erroneous identifications, all firearms and toolmark identifications should be excluded until adequate statistical empirical foundations and profiency testing are developed for the field.